2020
DOI: 10.1038/s41419-020-02981-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress promotes EMT-mediated metastasis through activation of STAT3 signaling pathway by miR-337-3p in breast cancer

Abstract: Chronic stress could induce cancer metastasis by constant activation of the sympathetic nervous system, while cellular mechanism remains obscure. The aim of this research is to explore the metastasis associated negative effect of chronic stress. The analysis of transcriptome sequencing implied that activation of STAT3 signaling pathway by downregulated miR-337-3p might be a potential mechanism to induce epithelial to mesenchymal transition (EMT) of cancer cell and promote metastasis under chronic stress. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 59 publications
(68 reference statements)
2
47
1
Order By: Relevance
“…It is reported that diphenyl urea derivative could serve as an inhibitor on human lung cancer cell migration by disrupting EMT via Wnt/β-catenin and PI3K/Akt signaling ( 44 ). Research from Du et al demonstrated that chronic stress promotes EMT-mediated metastasis through activation of the STAT3 signaling pathway by miR-337-3p in breast cancer ( 45 ). The EMT signaling pathway, as an axis center, has been revealed to largely participate in the regulation of cancer metastasis ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that diphenyl urea derivative could serve as an inhibitor on human lung cancer cell migration by disrupting EMT via Wnt/β-catenin and PI3K/Akt signaling ( 44 ). Research from Du et al demonstrated that chronic stress promotes EMT-mediated metastasis through activation of the STAT3 signaling pathway by miR-337-3p in breast cancer ( 45 ). The EMT signaling pathway, as an axis center, has been revealed to largely participate in the regulation of cancer metastasis ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…When going for holistic cancer care [ 97 , 98 ], spiritual and emotional conditions are equally essential, alongside physical and social status ( Figure 7 ). Psychosocial stress is associated with cancer incidence [ 98 , 99 , 100 ], metastasis [ 99 , 101 , 102 , 103 ], and poor survival [ 104 ]. These impacts might be mediated through the hypothalamic–pituitary–adrenal (HPA) axis [ 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…All the mice received three kinds of behavior tests within the two weeks after the last stress stimulation, including the open field test, the tail suspension test and the sucrose preference test, following the procedures described in the literature [ 32 , 33 ]. A video tracking system (SuperMaze V2.0, Shanghai, China) was used to record and analyze the activity of mice in the open field test and tail suspension test.…”
Section: Methodsmentioning
confidence: 99%